2008
DOI: 10.1016/j.bjmsu.2008.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Polydimethylsiloxane in the Treatment of Sphincter Weakness Incontinence in Men with Spinal Cord Injury: Long-Term Follow-Up

Abstract: To assess the long-term effectiveness of polydimethylsiloxane (PDS, Macroplastique TM ) perisphincteric injections in treating male sphincter weakness incontinence (SWI) caused by spinal cord injury (SCI). Patients and methods: Fourteen male patients with SCI underwent PDS injection to the external urethral sphincter for SWI (mean age: 50.1 years; range: 32-79 years).A single surgeon at a specialist spinal injury unit managed all patients. Complete cure was defined as cessation of pad usage with no evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In fact, recruitment to the study was curtailed as the mean leakage, assessed by 24‐hour pad weight test, more than doubled during follow‐up compared to baseline. Similarly, poor outcomes were reported in a spinal cord injury population by Attar et al using Macroplastique. Both studies showed a moderate risk of bias.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…In fact, recruitment to the study was curtailed as the mean leakage, assessed by 24‐hour pad weight test, more than doubled during follow‐up compared to baseline. Similarly, poor outcomes were reported in a spinal cord injury population by Attar et al using Macroplastique. Both studies showed a moderate risk of bias.…”
Section: Resultsmentioning
confidence: 57%
“…The authors hypothesized that because of the older population group and iatrogenic neurovascular damage due to prostatectomy, the periurethral collagen could be less supportive . It should be noted, however, that Attar et al reported similarly high failure rates in a younger population in the absence of prostatic surgery.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations